Feasibility and acceptability of a peer-led HIV self-testing model among female sex workers in Malawi: a qualitative study - Miriam Taegtmeyer; Karin Hatzold; Elizabeth L Corbett; Nicola Desmond; Cheryl C Johnson; Richard Chilongosi; Moses K Kumwenda; Webster Mavhu; Wezzie S Lora; Simon Sikwese (BMJ Open)
Objectives HIV testing is the gateway to HIV prevention and care services. Female sex workers (FSW) may benefit from HIV self-testing (HIVST), which offers greater control and confidentiality than other approaches. However, FSW also have unique vulnerabilities, making it critical to understand their perspective of HIVST to best contextualise HIVST to their needs. This study explored feasibility and acceptability of providing oral fluid-based peer-led HIVST to FSW to inform tailored HIVST delivery approaches.Design Qualitative study.Setting Malawi.Participants Thirty-nine FSW who had obtained a HIVST kit and eight peer distributors.Results Peer distributors’ accounts suggested that peer-led HIVST is feasible. Overall, FSW spoke positively about peer-led HIVST and younger FSW preferred it to facility-based HIV testing. FSW highlighted both greater control of their testing experience and that HIVST could allow them to avoid discriminatory attitudes frequently experienced in public facilities. Some also felt that HIVST kits could enable them to establish the HIV status of their sexual partners, better informing their decisions about condomless sex. Despite overall acceptance of HIVST, a few expressed doubts in the procedure. Some FSW already aware of their HIV-positive status reported using HIVST. A few accounts suggested peer pressure to self-test predominantly from peer distributors.Conclusions This study enabled us to explore feasibility and acceptability of peer-led HIVST among FSW, as well as potential shortcomings of the HIV testing modality. Peer distributors are a welcome additional model. However, they should avoid distribution in actual venues. Programmes should ensure a range of testing options are available and expand peer’s representation. Study findings will be used to tailor the HIVST distribution model to ensure its enhanced uptake among key populations in general and FSW, specifically.